Educação matemática em escolas inclusivas: a sala de recursos em destaque - Hilsdorf, Carla Regina Riani [UNESP] (2014)
This dissertation presents a research based on the question: What are the demands and potentials of working in a resource room by the time of teaching mathematics in inclusive schools? The study was conducted in a primary school, and aimed to investigate possibilities of teachers working at the resource room during the process of teaching and learning mathematics for children with special needs. Counting problems were used as a resource for intervention, which had been worked previously at the resource room in individual sessions, and later at the classroom with the students. We chose to do an intervention that could approach an ideal situation, previously introducing a math content in individualized sessions in a resource room that would later be worked into the regular classroom. That was done with included students, properly diagnosed and who were seen, at a health facility, by various specialists aiming the best development of their skills. Data were obtained through filming, photos and notes, besides interviews with inclusion classes' teachers. The analysis indicated that the way the intervention was performed resulted in several potentialities for the development of the children, amid them, the importance of dialogic situation as mediation and, showing that the difficulties presented by the students are working tools for the resource room teacher, as he or she can understand their needs and work towards meeting them. Tied to this fact the results indicated several demands for the resource room teacher as the importance of planning activities and work in partnership with teachers of regular classes. Based on what has been seen about the students during this study, and established contact with the inclusion classes' teachers, it was observed that it is possible for the teacher from the resource room to create math education environments that are inclusive and motivating, providing to the regular class teacher ideas and resources in...